2015
DOI: 10.1123/jsm.2013-0259
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Urban Development Through a Sport Events Portfolio: A Case Study of London, Ontario

Abstract: This study investigates the underdeveloped area of event portfolios in an attempt to fill a gap in the existing literature. This research article examines strategic positioning of events and the critical role they play in local development. To understand this, a case study design was performed in a medium-sized city in Canada. The purpose of the study was to determine how the city has used sport events for broader local development and enhancement of the civic brand. Interviews with local city actors and docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 34 publications
1
65
1
Order By: Relevance
“…Benefits of sporting events include, for example, economic, community, recreation and tourism benefits as well as increased employment, social and human capital and city improvements (Clark and Misener, 2015). Moreover, increased cultural identity and social interaction opportunities are also positive impacts of sports tourism practices (Hritz and Ross, 2010).…”
Section: Sports Tourism and Regional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits of sporting events include, for example, economic, community, recreation and tourism benefits as well as increased employment, social and human capital and city improvements (Clark and Misener, 2015). Moreover, increased cultural identity and social interaction opportunities are also positive impacts of sports tourism practices (Hritz and Ross, 2010).…”
Section: Sports Tourism and Regional Developmentmentioning
confidence: 99%
“…Although studies have found evidence of positive impacts of sports tourism (see Ap 1992;Brida and Disegna 2011;Chen 2008;Coakley 2004;Costa and Chalip 2005) for broader civic and local development of hosting cities, and it is commonly assumed that this will create lasting economic benefits to destination cities (Demir et al, 2015), long-term social benefits for host regions seems improbable and are not guaranteed (Clark and Misener, 2015). Instead, literature has evidenced that the long-term benefits are increased international publicity and recognition; in other words, image promotion (Demir et al, 2015), and that these marketing benefits are volatile in time (Demir et al, 2015;Chen 2008;Coakley 2004) There seems to clearly exist limitations for regions to maintain the benefits on a longterm basis.…”
Section: Sports Tourism and Regional Developmentmentioning
confidence: 99%
“…This structure entails local governance and administrative systems which facilitate the incorporation of events into policy agendas and foster collaboration between event stakeholders and policy-making agents. As the literature demonstrates, although, cities may have some elements of a portfolio approach, a lack of connectivity and institutional structure stops them from a sustainable and synergetic portfolio development (Clark & Misener, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More specifically, by identifying local needs and opportunities as well as external forces that might influence the portfolio nature (e.g., political, economic, legal, or environmental issues), city event planners could design portfolios that would reflect the unique and authentic conditions of a host destination. There is still insufficient research that is focused on examining local settings and public processes, which may determine the development of event strategies and portfolio approaches (Antchak, 2017, Clark & Misener, 2015Dragin-Jensen et al 2016;Ziakas, 2007). Local institutional and community contexts where portfolios operate should be holistically scrutinized in order to understand the complexities of event-related processes in cities and their unique set of developmental needs that a portfolio of events might be able to satisfy.…”
Section: Comparing Approaches To Event Portfolio Design 549mentioning
confidence: 99%